Ultrasound for Non-invasive Assessment and Monitoring of Quadriceps Muscle Thickness in Critically Ill Patients With Acute Kidney Injury - Sabatino, Alice; Maggiore, Umberto; Regolisti, Giuseppe; Rossi, Giovanni Maria; Di Mario, Francesca; Gentile, Micaela; Farina, Maria Teresa; Fiaccadori, Enrico (Frontiers in Nutrition, 2021)
Background and aims: Critically ill patients with acute kidney injury (AKI) undergo major muscle wasting in the first few days of ICU stay. An important concern in this clinical setting is the lack of adequate tools for routine bedside evaluation of the skeletal muscle mass, both for the determination of nutritional status at admission, and for monitoring. In this regard, the present study aims to ascertain if ultrasound (US) is able to detect changes in quadriceps muscle thickness of critically ill patients with acute kidney injury (AKI) over short periods of time. Methods: This is a prospective observational study with a follow-up at 5 days. All adult patients with AKI hospitalized at the Renal ICU of the Parma University Hospital over 12 months, with a hospital stay before ICU admission no longer than 72h, and with a planned ICU stay of at least 5 days, were eligible for the study. An experienced investigator assessed quadriceps rectus femoris and vastus intermedius thickness (QRFT and QVIT) at baseline and after 5 days of ICU stay. Results: We enrolled 30 patients with 74 ± 11 years of age and APACHE II score of 22 ± 5. Muscle thickness decreased by 15% ± 13% within the first 5 days of ICU stay (P < 0.001 for all sites as compared to ICU admission). Patients with more severe muscle loss had a higher probability of prolonged hospitalization. Conclusions: In critically ill patients with AKI, bedside muscle US identifies patients with accelerated muscle wasting.